The impact of city contracting set-asides on black self-employment and employment - Aaron K. Chatterji; Kenneth Y. Chay; Robert W. Fairlie (Institute for the Study of Labor (IZA), 2013)
In the 1980s, many U.S. cities initiated programs reserving a proportion of government contracts for minority-owned businesses. The staggered introduction of these set-aside programs is used to estimate their impacts on the self-employment and employment rates of African-American men. Black business ownership rates increased significantly after program initiation, with the black-white gap falling three percentage points. The evidence that the racial gap in employment also fell is less clear as it is depends on assumptions about the continuation of pre-existing trends. The black gains were concentrated in industries heavily affected by set-asides and mostly benefited the better educated.
Keywords: J15; L26; 330; entrepreneurship; self-employment; race; black; African-American; contracting; affirmative action